Pengaruh Pengembangan Sumber Daya Manusia Serta Pemberian Motivasi terhadap Kinerja Karyawan di PT Istana Putra Astaguna - Silvy Eka Ratna Sari; Soni Harsono (Ekonomis: Journal of Economics and Business, 2023)
This study aims to examine the effect of human resource development and motivation on employee performance at Pt. Istana Putra Astaguna the research sample consists of 100. Then there are characteristics of the vulnerable age of 17-60 years. This sampling technique uses purposive sampling because only productive employees are taken. Analysis used validity, reliability, descriptive statistical analysis, multiple linear regression, and hypothesis testing and data collection using a questionnaire in the form of Google Form. The results of this study indicate that human resource development has a partial effect on employee performance. Motivation has a partial effect on employee performance. Human resource development and motivation simultaneously have an effect on employee performance.